2020
DOI: 10.1002/slct.201904697
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrimidine Derivatives Catalyzed by Nanomagnetic Pyridinium‐Tribromide Ionic Liquid

Abstract: Some novel pyrimidine derivatives are prepared via one-pot reaction of triethoxymethane, aromatic ketone and ammonium acetate using catalytic system including nano-magnetic pyridinium-tribromide (TBP-SCMNPs). The synthesized new catalyst was characterized by FE-SEM, EDS, TEM, XRD, and TGA analysis. The highlighting points of using TBP-SCMNPs are easy purification, reusability of the catalyst, good yields of products with short time reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[24,25] The liquid-liquid biphasic catalysis system has received much attention, and the possibility of using this technology in industrial processes is being investigated by many researchers. [15,26] In recent decades the ILs have attracted much attention because of their extensive applications in organic synthesis, [27][28][29][30][31][32][33] catalytic oligomerization of ethylene, [4,17,25] chemical separation, [34][35][36] material, and energy science. [37,38] For example, the chloroaluminate IL has been used as solvents in ethylene oligomerization reactions in the presence of nickel complexes to overcome the deactivation of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] The liquid-liquid biphasic catalysis system has received much attention, and the possibility of using this technology in industrial processes is being investigated by many researchers. [15,26] In recent decades the ILs have attracted much attention because of their extensive applications in organic synthesis, [27][28][29][30][31][32][33] catalytic oligomerization of ethylene, [4,17,25] chemical separation, [34][35][36] material, and energy science. [37,38] For example, the chloroaluminate IL has been used as solvents in ethylene oligomerization reactions in the presence of nickel complexes to overcome the deactivation of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…222 Recently, they also reported pyridinium tribromide ionic liquid-supported silica coated ferrite NPs for the efficient synthesis of 4-phenyl pyrimidines from triethoxy methane, ammonium acetate and substituted acetophenones. 223 Yavari et al reported the synthesis of 2-aryl imidazoles (83g)/ benzothiazoles (204a)/benzimidazoles (83h)/spermidine (206) derivatives via cyclocondensation with aromatic aldehydes catalyzed by functionalized magnetic core NPs (Fe 3 O 4 /SiO 2 / (CH 2 ) 3 N + Me 3 Br 3 ) under solvent-free conditions at 80 C in 89-95% yield (Scheme 108). 224 The NPs were prepared via the coprecipitation of ferrous (FeSO 4 $7H 2 O) and ferric salts (FeCl 3 -$7H 2 O) with NH 4 OH followed by coating with silica using the Stöber process, graing with aminopropylsilanes and coupling with methyl iodide and tribromide (KBr/Br 2 ).…”
Section: Fenp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…The catalyst had a good reactivity due to the appropriate concentration of bromine and had little degradation during the reaction. Then from ionic liquid-based nano-magnetic (MNPs@SiO 2 -Pr-AP-tribromide) [53] to synthesize quinoline derivatives 3(a-i), we used a one-pot reaction between 2-amino aryl ketones (1) and carbonyl compounds (2) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%